The Psychology of Communication in Constructing the Self-Concept of Crossdressing Cosplayers - Ardiansyah, Muhammad Rafli; Mustiawan; Tiara, Andys (Journal of Communication Studies, 2025)
This study analyzes how communication psychology plays a role in shaping the self-concept of individuals who practice cross-dressing within the cosplay community in Indonesia. This phenomenon gives rise to complex identity dynamics, as it directly intersects with cultural norms that tend to be conservative toward non-binary gender expressions. The study employed a qualitative approach with a descriptive method. Informants were selected using purposive sampling techniques based on their consistency in cross-dressing cosplay and active involvement within the community. Data collection techniques included  in-depth interviews, participatory observation, and literature review. The results show that the psychological communication process in cross-dressing cosplay involves intrapersonal communication through identity reflection, social support from the community, and reinforcement from social media despite the presence of cultural conflicts and norms attached to gender issues. Crossdressing is positioned not merely as a form of artistic performance but as a symbolic strategy to express, test, and negotiate self-identity within a social space that is not yet fully inclusive. These findings confirm that self-identity is a communicative construct that is dynamic, contextual, and potentially subversive to dominant norms. This study makes an important contribution to the development of communication psychology studies in the domains of alternative identity expression and popular culture. The limitation of this research lies in the small number of participants and the narrow geographic scope; thus, further research with a larger participant base and multi-location approaches is necessary for more comprehensive results.